CD68+ Macrophage Infiltration Associates With Poor Outcome of HPV Negative Oral Squamous Carcinoma Patients Receiving Radiation: Poly(I:C) Enhances Radiosensitivity of CAL-27 Cells but Promotes Macrophage Recruitment Through HMGB1 - Ai, Dan; Dou, Yu; Nan, Zhaodi; Wang, Ketao; Wang, Huayang; Zhang, Lin; Dong, Zuoqing; Sun, Jintang; Ma, Chao; Tan, Wanye; Gao, Wenjuan; Liu, Jia; et al. (Frontiers in Oncology, 2021)
Patients with Human Papillomavirus (HPV) negative oral squamous cell carcinoma (OSCC) generally have poor clinical outcomes and worse responses to radiotherapy. It is urgent to explore the underlining mechanisms of the distinct prognoses between HPV negative and HPV positive OSCC and to develop effective therapy strategy to increase the survival rate of HPV negative OSCC patients. We conducted a retrospective cohort of 99 resected OSCC patients to evaluate the prognosis of HPV negative and HPV positive OSCC patients receiving radiation or not. We further addressed the association of CD68+ macrophage infiltration with HPV status and the effects on survival of OSCC patients. We also used the TCGA-OSCC cohort for further verification. Based on the cohort study, we applied a synthetic dsRNA polymer, polyriboinosinic-polyribocytidylic acid (poly(I:C)) on CAL-27 (HPV negative OSCC cells). We co-cultured its condition medium with THP-1 derived macrophage and examined the cytokines and macrophage migration. We found that high CD68+ macrophage infiltration associated with poor overall survival in HPV negative OSCC patients receiving radiation. In vitro, poly(I:C) could induce apoptosis and enhance the radiosensitivity, but increase macrophage recruitment. Targeting HMGB1 could inhibit IL-6 induction and macrophage recruitment. Our findings indicated that CD68+ macrophage might play an important role in the outcomes of HPV negative OSCC patients receiving radiation. Our findings also suggested that radiation combined poly(I:C) might be a potential therapy strategy to increase the radiation response and prognosis of HPV negative OSCC. Notably, HMGB1 should be targeted to inhibit macrophage recruitment and enhance overall therapy effects.